Unraveling the periprandial changes in brain serotonergic activity and its correlation with food intake-related neuropeptides in rainbow trout Oncorhynchus mykiss - Chivite, Mauro; Ceinos, Rosa M.; Cerdá-Reverter, José M.; Soengas, Jose L.; Aldegunde, Manuel; López-Patiño, Marcos A.; Míguez, Jesús M. (Frontiers in Endocrinology, 2023)
This study explored changes in brain serotonin content and activity together with hypothalamic neuropeptide mRNA abundance around feeding time in rainbow trout, as well as the effect of one-day fasting. Groups of trout fed at two (ZT2) and six (ZT6) hours after lights on were sampled from 90 minutes before to 240 minutes after feeding, while additional groups of non-fed trout were also included in the study. Changes in brain amine and metabolite contents were measured in hindbrain, diencephalon and telencephalon, while in the diencephalon the mRNA abundance of tryptophan hydroxylase (tph1, tph2), serotonin receptors (5htr1a, 5htr1b and 5htr2c) and several neuropeptides (npy, agrp1, cartpt, pomca1, crfb) involved in the control of food intake were also assessed. The results showed changes in the hypothalamic neuropeptides that were consistent with the expected role for each in the regulation of food intake in rainbow trout. Serotonergic activity increased rapidly at the time of food intake in the diencephalon and hindbrain and remained high for much of the postprandial period. This increase in serotonin abundance was concomitant with elevated levels of pomca1 mRNA in the diencephalon, suggesting that serotonin might act on brain neuropeptides to promote a satiety profile. Furthermore, serotonin synthesis and neuronal activity appear to increase already before the time of feeding, suggesting additional functions for this amine before and during food intake.Exploration of serotonin receptors in the diencephalon revealed only small changes for gene expression of 5htr1b and 5htr2c receptors during the postprandial phase. Therefore, the results suggest that serotonin may play a relevant role in the regulation of feeding behavior in rainbow trout during periprandial time, but a better understanding of its interaction with brain centers involved in receiving and processing food-related signals is still needed.